(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of 2.5% mafenide acetate (MA) solution in controlling multidrug-resistant Pseudomonas aeruginosa infection in experimental burn wounds. Methods: A prospective study was conducted on 60 healthy rabbits with experimentally induced burn wounds, divided into six groups: MA 2.5% produced by Hanoi University of Pharmacy (MA2.5-A), MA 2.5% produced in the United States (MA2.5-B), 0.9% normal saline (NA), MA 5% produced by Hanoi University of Pharmacy (MA5-A), MA 5% produced in the United States (MA5-B), and 0.1% berberine solution (BE). Results: On days 7 and 10, Pseudomonas aeruginosa CFU counts and culture positivity rates in the MA2.5-A group were comparable to those in the MA2.5-B and MA5 groups (p > 0.05). By day 14, no Pseudomonas aeruginosa growth was detected in any MA-treated groups. At days 7, 10, and 14, CFU counts in all MA groups were significantly lower than those observed on day 3 (p < 0.05). Compared with the NA and BE groups, both CFU counts and culture positivity rates of Pseudomonas aeruginosa were significantly reduced in all MA groups at days 7, 10, and 14 (p < 0.05). Conclusion: The topical infection control efficacy of 2.5% and 5% mafenide acetate solutions is comparable.